DAMPAK PENAMBANGAN GAMBUT TERHADAP BIODIVERSITAS IKAN DI KABUPATEN BENGKALIS, RIAU - Haryono Haryono; Agus H Tjakrawidjaja (BERITA BIOLOGI, 2000)
A study on peat mining impact on fish diversity was conducted at Perawang, Bengkalis Regency,Province of Riau between 1996 and 1997.The purpose of study is to discover the diversity and potential of fishes in relation with water quality due to peat mining activities.The results recorded 17 species belonging to 14 genus and 10 families in mining areas, while in the protected areas (with 3 Watersheds) recorded 4 species in Bukit Batu, 21 species in Siak Kecil and 17 species in Kampar.Cyprinidae is dominant family in mining areas, while Belontiidae in protected areas.The water quality ranges are DO between 0.49 and 4.60 ppm, CO2 between 2.31 and 26.36 ppm, pH between 3.80 and 4.80 and turbidity 1.40 and 4.20. The potential offish found are mainly consumption and ornamental fish.